A clinical study of maternal outcome among pregnant mothers suffering from preeclampsia with thrombocytopenia - H. S., Kavyashree; K., Rajeshwari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The thrombocytopenia in preeclampsia is mild to moderate, but severe thrombocytopenia can occur. Patients with eclampsia were at even greater risk for developing severe thrombocytopenia. And more likely to have HELLP syndrome, which is a subset of preeclampsia. Thrombocytopenia is a key and necessary component of this syndrome. The objective of the present study was to observe a clinical study of maternal outcome among pregnant mothers suffering from preeclampsia with thrombocytopenia. Methods: A Hospital based Study was conducted at Mysore Medical College from January 2018 to December 20180 in the department of Obstetrics and gynecology. A total of 100 cases of Pregnancy from the records / case sheets of pregnant women with pregnancy induced hypertension admitted in the labor ward of the department of obstetrics and gynecology, Mysore Medical College, Mysore, Karnataka, India. Results: Majority of the study subjects in present study were aged between 21-25 years (42%) followed by <20 years (26%). Nearly 55% of the study group were prim parous. In the above table out of 100 cases included in the study, 28 and 40 cases presented with mild and severe pregnancy induced hypertension, 8 cases were diagnosed as eclampsia and 24 cases presented with HELLP syndrome. The association between the mode of delivery and the variants of PIH was found to be statistically not significant. The Association between Mode of delivery and gestation weeks among the eclampsia cases was found to be not significant. Conclusions: Thrombocytopenia in pregnancy induced hypertension carries a risk for both the mother and her fetus. The associated causes like abruption, retain dead fetus, septicemia and disseminated intravascular coagulation aggravates the complication for thrombocytopenia.